INNOVATIVE LOGISTICS STRATEGY AS AN EFFECTIVE MEANS FOR OPTIMIZING THE BUSINESS PROCESSES OF INDUSTRIAL ENTERPRISES - Malahat Soltan Huseynova; Zulfiya Elman Hajiyeva; Zulfiya Mirza Gasimova; Saida Rahim Mammadova (Academy Review)
Today, a pressing issue for industrial enterprises is the development of an innovative logistics strategy on an efficient basis, especially the use or application of more modern supply chain management methods to increase competitiveness. On the one hand, such a strategy involves high costs for the implementation of innovations in logistics, on the other hand, it is an important tool for optimizing the business processes of enterprises and increasing their economic efficiency. In modern conditions, simply employing a logistical approach in the operation of industrial enterprises is insufficient for optimizing business processes. There is a clear need for methodological tools to ensure the effective application of innovative logistics. Innovative logistics plays a crucial role in improving service quality, reducing the total costs associated with flow processes and increasing their efficiency. Relevance of the topic. In modern times, industrial enterprises play a critical role in ensuring the sustainability of a country’s development. Therefore, it is essential to foster the growth of these enterprises, which requires the implementation of effective mechanisms. One such mechanism is the application of an innovative logistics strategy. Innovative logistics facilitates the organization of flow processes, enables the evaluation of management effectiveness through analysis, identifies and utilizes resources, and ultimately enhances the overall efficiency of the enterprise. Given that an innovative logistics strategy can help optimize business processes in industrial enterprises by employing innovative mechanisms, tools, and methods to manage logistics flows and add value within supply chains, research in this area is highly important. The purpose of the article is to determine the role of innovative logistics strategy as one of the most important and effective tools for the business processes of industrial enterprises. Additionally, the article aims to investigate the mechanism of implementation of innovative logistics strategies to optimize business processes in industrial enterprises and achieve economic effect. An in-depth study of consumer preferences, market development prospects, and scientific and technical opportunities is identified as a critical condition for optimizing business processes in industrial enterprises. Such factors can assist enterprise management in developing a logistics flow management strategy that will provide the necessary conditions for business activity. Under such circumstances, enterprises will have the opportunity to apply and actively develop innovative methods and tools to manage those flows. Research methods. Comparison, development dynamics, generalization, grouping, factor analysis, economic-statistical analysis. Scientific innovation. The article demonstrates that an innovative logistics strategy is a long- term direction for the development of logistics, directly influencing the business processes of industrial enterprises. It was established that developing such a strategy by the higher management bodies of industrial enterprises, aligned with their goals, can optimize the use of all resources in managing logistics flows. Furthermore, it was found that the application of innovations in logistics can enhance the financial stability of the enterprise, improve service quality, and provide competitive advantages by delivering products to the final consumer more quickly and at a lower cost. As a result of the research, specific directions for the effective implementation of innovative logistics strategies, which can play a significant role in optimizing business processes within enterprises, have been proposed.